Biological activity of pomegranate peel for the green management of Ephestia kuehniella (Lepidoptera: Pyralidae) larvae - Federica Lo Muzio; Onofrio Marco Pistillo; Ilaria D'Isita; Giovanni Iadarola; Giuseppe Rotundo; Antonella Di Palma; Antonio De Cristofaro; Nickolas G. Kavallieratos; Maria C. Boukouvala; Giacinto Salvatore Germinara (Crop Protection, 2026)

Is the unavailability of rifapentine holding back the end TB strategy in Europe? Implication for tuberculosis control among migrants and refugees - Salvatore Rotundo; Francesca Serapide; Giacomo Guido; Francesco Di Gennaro; Alessandro Russo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Managing tuberculosis infection among migrants from high-incidence tuberculosis countries: challenges, strategies and recommendations - Salvatore Rotundo; Francesca Serapide; Gabriella d’Ettorre; Maria Teresa Tassone; Mattia Albanese; Gabriella Giuseppina Marino; Bruno Tassone; Giancarlo Ceccarelli; Alessandro Russo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Tuberculosis (TB) remains a significant global health challenge, especially in countries with low TB incidence, exacerbated by the influx of migrants from high TB-burden regions. This paper reviews the challenges and strategies for managing TB infection (TBI) among migrants. Challenges in screening and treating TBI among migrants include diagnostic limitations of available tests which are tuberculin skin test (TST) and interferon-gamma release assay (IGRA), socioeconomic barriers, cultural beliefs and mobility. Recommendations vary among guidelines, ranging from proactive screening to targeted approaches. We addressed the issue of two-step testing, discussing the use of an initial TST followed by IGRA confirmation, with consideration of BCG vaccination status and TB exposure history. Treatment options for TBI include isoniazid monotherapy and rifamycin-based regimens in most cases, with varying preferences across guidelines. Challenges in TBI treatment include hepatotoxicity and adherence issues, particularly among migrants. Overall, a comprehensive approach addressing socioeconomic, cultural, and structural factors is crucial for effective TBI management among migrants. Collaboration between healthcare providers, policymakers and migrant communities is essential for developing culturally sensitive screening and treatment protocols. Further research is needed to evaluate the efficacy and feasibility of different screening and treatment strategies, particularly among migrant populations.

Climate and landscape composition explain agronomic practices, pesticide use and grape yield in vineyards across Italy - Costanza Geppert; Mariana da Cruz; Alberto Alma; Lucia Andretta; Gianfranco Anfora; Donatella Battaglia; Giovanni Burgio; Vittoria Caccavo; Serena Giorgia Chiesa; Francesca Cinquatti; Arturo Cocco; Elena Costi; et al. (Agricultural Systems, 2024)

Repellents effectively disrupt the olfactory orientation of Sitophilus granarius to wheat kernels - Giacinto Salvatore Germinara; Antonio De Cristofaro; Giuseppe Rotundo (Journal of Pest Science, 2015)

Chemical, Electrophysiological, and Behavioral Investigations on the Sex Pheromone of Lackey Moth, Malacosoma neustrium - Giuseppe Rotundo; Giacinto Salvatore Germinara; Antonio De Cristofaro (Journal of Chemical Ecology, 2004)